Social Network Analysis Percakapan Pengguna X seputar Isu Pengungsi Rohingya di Indonesia - Dahana, Abyzan Syahadin Bagja (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study aims to explore the X conversation network around the issue of Rohingya refugees in Indonesia. The Rohingya are one of the few ethnic Muslims who, since 2009, have sailed to Indonesia from their home country of Myanmar to seek asylum due to horizontal conflict. This phenomenon also caught the attention of netizens in Indonesia as one of the network community entities. This study used a total of 80,924 datasets in the form of original tweets along with replies and amplifications in the form of retweets that appeared throughout November to December 2023 to build a visualization of the X conversation network around the issue of Rohingya refugees. This study adopts the social network analysis (SNA) method to see influential actors based on the degree centrality measurement metric. In addition, researchers also applied sentiment analysis to identify the sentiment in the original tweet. SNA points out that four accounts of ordinary citizens and one account of informational media (neohistoria_id) dominate the conversation network. Meanwhile, sentiment analysis showed that conversations around the issue of Rohingya refugees in Indonesia were dominated by negative tweets of rejection. The bad stigma that X users raise against Rohingya refugees is linked to mass media reports or hoax information that describes the bad behavior of Rohingya refugees.